Effects of Particle Size and Morphology on Filtration of Airborne Nanoparticles - Jing Wang (KONA Powder and Particle Journal, 2013)
The rapid development of nanotechnology brings new challenges to aerosol filtration, which plays a critical role in controlling pollution and protecting the environment and human health. The filtration of airborne nanoparticles is becoming an important issue as they are produced in large quantities from material synthesis and combustion emission. Recent studies indicate that the filtration efficiency increases as the particle size decreases down to 2 – 3 nm. Thus the conventional filters are working well against the nanoparticles. The filtration of non-spherical nanomaterials, such as carbon nanotubes and nanoparticle agglomerates, possesses different filtration characteristics compared to spherical particles. The interception effect for elongated particles is stronger than for spheres with the same mobility, thus higher filtration efficiency is achieved. Modeling results based on the single-fiber theory are compared to experimental data and then used to predict the difference between the filter penetrations for agglomerates and spheres. The effects of the filtration velocity, filter fiber size, solidity and thickness are systematically investigated.